2020
DOI: 10.1177/2280800020926615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Conditioning on the Repair Strength of Bioactive Restorative Material

Abstract: Objective: To evaluate the effects of surface treatment and repair material on the repair shear bond strength (SBS) of the bioactive restorative material. Methods: A total of 240 Activa BioActive Restorative (Activa) discs were prepared, aged, and polished, and divided randomly into eight groups ( n = 30). Groups 1–4 discs were repaired with bulk-fill flowable resin-based composite (Bulk-RBC), and Groups 5–8 discs with Activa. Surface treatment used for each repair material type were air abrasion with silica-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Several chemical or mechanical surface treatment methods, such as sandblasting using a microetcher, and the application of hydrofluoric acid, silane, adhesive, or a combination of these, have been recommended. 25 , 33 , 34 , 35 However, sandblasting and the application of hydrofluoric acid are not ideal methods to execute intraorally. Besides, it is more favorable to carry out a simple procedure rather than a complicated one in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several chemical or mechanical surface treatment methods, such as sandblasting using a microetcher, and the application of hydrofluoric acid, silane, adhesive, or a combination of these, have been recommended. 25 , 33 , 34 , 35 However, sandblasting and the application of hydrofluoric acid are not ideal methods to execute intraorally. Besides, it is more favorable to carry out a simple procedure rather than a complicated one in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In repair procedures, the union between a new resin and the aged one occurs through the chemical union between the organic matrix and/or through mechanical retention [ 21 ]. The challenges associated to this procedure remains over the fact that the surface of the aged composites lacks any unreacted double bonds available for bonding to the new composite [ 18 , 27 ]. The use of physical or chemical procedures, such as sandblasting, bur abrasion, acid etching (hydrofluoric or phosphoric acids) among others, aims to remove the outermost surface layer, which is altered by the saliva, oral films, and by the natural aging of the restoration, thus increasing the external layer surface energy and surface area and creating micro-irregularities [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repairs of partly defective restorations are indicated for resin-based composites (RBCs) aiming to increase the longevity of the restoration and consequently the tooth, being part of the minimally invasive dentistry philosophy [8]. e repairs involve partial removal of the defective part of the restoration, which is then replaced using a new material, and therefore, the knowledge of the composition of the resin composite is crucial for its success [26,27]. One recent clinical trial showed that the performance of repaired restorations was similar to replaced ones in terms of marginal adaptation, secondary caries, color, and anatomy [28], encouraging its indication, even though literature is still controversial in the most effective technique to perform them, mainly regarding the requirement for surface treatments [8,18,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Following the shear bond strength testing, all specimens were assessed by one trained examiner using an optical microscope (Stereomicroscope) at x25 magnification for the mode of failure which was identified as adhesive, cohesive or mixed (adhesive and cohesive) (27).…”
Section: Marginal Adaptation Testmentioning
confidence: 99%